2008
DOI: 10.1016/j.concog.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Visual motion disambiguation by a subliminal sound

Abstract: To cite this version:A. Dufour, P. Touzalin, M. Moessinger, Renaud Brochard, O. Després. Visual motion disambiguation by a subliminal sound. Consciousness and Cognition, Elsevier, 2008, 3 (17) AbstractThere is growing interest in the effect of sound on visual motion perception. One model involves the illusion created when two identical objects moving towards each other on a two-dimensional visual display can be seen to either bounce off or stream through each other. Previous studies show that the large bias n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Even though the StdSBD is physically simultaneous with a tone and the coincidence and the tone is apparently integrated, our results show that a tone that is spatiotemporally proximate to the coincidence of the TstSBD exerts an influence on the percept of the TstSBD, possibly by distracting the (attentive) tracking of visual motion. Moreover, a sensory transient due to a sudden physical change is considered to draw our attention to a location of interest (Kanai & Verstraten, 2004) although Dufour, Touzalin, Moessinger, Brochard, and Després (2008) reported audiovisual bouncing effect in the absence of conscious perception of an auditory transient. Nevertheless, the balance of evidence to date on the stream/bounce effect favors the attentional distraction account.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the StdSBD is physically simultaneous with a tone and the coincidence and the tone is apparently integrated, our results show that a tone that is spatiotemporally proximate to the coincidence of the TstSBD exerts an influence on the percept of the TstSBD, possibly by distracting the (attentive) tracking of visual motion. Moreover, a sensory transient due to a sudden physical change is considered to draw our attention to a location of interest (Kanai & Verstraten, 2004) although Dufour, Touzalin, Moessinger, Brochard, and Després (2008) reported audiovisual bouncing effect in the absence of conscious perception of an auditory transient. Nevertheless, the balance of evidence to date on the stream/bounce effect favors the attentional distraction account.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the case of sequence learning, the sequences can be relatively simple, involving only first-order relations (Atas, Faivre, Timmermans, Cleeremans, & Kouider, 2014), or more complex (Rosenthal, Andrews, Antoniades, Kennard, & Soto, 2016;Rosenthal, Kennard, & Soto, 2010). Cross-modal effects where one of the stimuli is subliminal have been observed in the case of visual motion disambiguation (Dufour, Touzalin, Moessinger, Brochard, & Després, 2008) and cross-modal priming (Lamy, Mudrik, & Deouell, 2008; though see Kouider & Dupoux, 2001). There have been some related cross-modal findings involving olfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some investigators have preferred to investigate subliminal effects at an objective threshold where forced-choice performance is at chance (e.g. Draine & Greenwald, 1998;Snodgrass & Shevrin, 2006). Even utilising objective methods the relationship between exposure and priming is not always straightforward, with some evidence that it can vary non-monotonically with SOA (Dagenbach, Carr, Wilhelmsen, 1989) and be subject to variations induced by the threshold setting tasks themselves (Carr & Dagenbach, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies found that removal of attention alone can not account for the effect, as some concurrent events presented at disks’ coincidence did not increase the proportion of bouncing percepts, while still distracting attention from the moving disks (Sekuler et al, 1997; Watanabe and Shimojo, 2001; Grassi and Casco, 2009). In addition, Dufour et al (2008) showed that the presentation of a subliminal sound, an event that was unlikely to have disrupted sustained attention, also promoted the bouncing percept. Therefore, it is unlikely that differences in sustained attention can fully explain the weakened effects of the visual and auditory events.…”
Section: Discussionmentioning
confidence: 99%